The Theory of Differential Overqualification: Does it Work? - Felix Büchel; Harminder Battu (Institute for the Study of Labor (IZA), 2002)
The theory of differential overqualification, developed by Robert Frank (1978), claims that married women in smaller labor markets have a higher risk of working in jobs for which they are overqualified. This stems from the problem of dual job search for couples which is much more difficult to optimize than single job search. Here, for several reasons husbands tend to first optimize their individual job search. Their wives are "tied movers" or "tied stayers" in the sense that their job search is undertaken under the condition that the job search of their husbands is optimized. This leads especially in smaller labor markets to a higher risk of a mismatch between formal qualifications and job requirements. The only specific empirical test of this theory, until now, has been performed by McGoldrick and Robst (1996). Their results, using US data, do not support the theory. Using German panel data (GSOEP), we also test the theory of differential overqualification. Unlike previous studies we control for commuting distances and our own results provide some mixed support for the differential overqualification hypothesis.
Keywords: J24; J16; J61; I21; 330; overqualification; regional migration; marriage; gender; Überqualifikation; Frauenerwerbstätigkeit; Familienökonomik; Arbeitsuche; Regionaler Arbeitsmarkt; Geschlecht; Schätzung; Deutschland